Tailored one anastomosis gastric bypass – Subgroup analysis of a randomised control trial based on bilio-pancreatic limb length with long-term results of 101 patients - Mayank Jain; Om Tantia; Ghanshyam Goyal; Tamonas Chaudhuri; Shashi Khanna; Anshuman Poddar; Kajari Majumdar; Sonam Gupta (Journal of Minimal Access Surgery, 2022)
Background: Ideal bilio-pancreatic limb (BPL) length is a highly debatable issue in one anastomosis gastric bypass (OAGB). Whether to use a tailored BPL or a fixed-length BPL needs to be answered. Materials and Methods: One-hundred and one patients who have undergone tailored OAGB based on basal metabolic index (BMI) and type 2 diabetes mellitus (T2DM) were analysed. Sixty-three patients had BPL of 150 cm and 38 patients had BPL of 180 cm. Mean pre-operative BMI of BPL 150 and 180 cm groups were 39.73 and 51.92 kg/m2, respectively. Results: There was a significant drop in mean total body weight, BMI and excess body weight of both the groups at 1 year which persisted for 5 years post-operatively. The mean BMI of BPL 150 and BPL 180 cm group at 5 years was 29.17 and 32.88 kg/m2, respectively. Although mean percentage excess weight loss (%EWL) and percentage of excess BMI loss in the two groups was similar, the mean percentage total weight loss (%TWL) was significantly higher for the BPL 180 cm group. There was no difference between the two groups in the number of patients who had >50% EWL and >20% TWL. At 5 years of follow-up, the mean serum iron level was significantly low in BPL 180 cm group. There was a significant drop in mean haemoglobin A1c values postoperatively, with no difference between the two groups. Conclusions: Tailored BPL of 150 and 180 cm do not show any difference in the number of patients achieving >50% EWL or >20% TWL and so increasing limb length may not increase the number of good responders for weight loss. Although the resolution of T2DM and improvement of QoL score do not change significantly with increase in BPL length, mean serum iron levels may be lower with longer BPL.